Commitment, Risk, and Consumption: Do Birds of a Feather Have Bigger Nests? - Shore, Stephen H; Sinai, Todd (The Review of Economics and Statistics, 2010)
Consumption commitments—goods like housing for which adjustment is costly—change the relationship between risk and consumption. Commitment provides a motive to reduce consumption when possible future losses are too small to warrant adjustment but not when losses are large enough that adjustment would be worthwhile. This implies conditions under which mean-preserving increases in risk can increase housing consumption. Our empirical evidence exploits the interaction of these conditions with a novel proxy for unemployment risk: couples sharing an occupation. Consistent with our model, same-occupation couples consume more housing only when adjustment costs are high and potential losses are sufficiently large.